Factors associated with hepatitis C virus RNA levels in early chronic infection: the InC3 study. Issue 9 (8th January 2015) - Hajarizadeh, B.; Grady, B.; Page, K.; Kim, A. Y.; McGovern, B. H.; Cox, A. L.; Rice, T. M.; Sacks‐Davis, R.; Bruneau, J.; Morris, M.; Amin, J.; Schinkel, J.; et al.
Summary Improved understanding of natural history of hepatitis C virus (HCV) RNA levels in chronic infection provides enhanced insights into immunopathogenesis of HCV and has implications for the clinical management of chronic HCV infection. This study assessed factors associated with HCV RNA levels during early chronic infection in a population with well‐defined early chronic HCV infection. Data were from an international collaboration of nine prospective cohorts studying acute HCV infection (InC3 study). Individuals with persistent HCV and detectable HCV RNA during early chronic infection (one year [±4 months] postinfection) were included. Distribution of HCV RNA levels during early chronic infection was compared by selected host and virological factors. A total of 308 individuals were included. Median HCV RNA levels were significantly higher among males (vs females; 5.15 vs 4.74 log IU/mL; P < 0.01) and among individuals with HIV co‐infection (vs no HIV; 5.89 vs 4.86; P = 0.02). In adjusted logistic regression, male sex (vs female, adjusted odds ratio [AOR]: 1.93; 95%CI: 1.01, 3.69), interferon lambda 4 (IFNL4) rs12979860 CC genotype (vs TT/CT; AOR: 2.48; 95%CI: 1.42, 4.35), HIV co‐infection (vs no HIV; AOR: 3.27; 95%CI: 1.35, 7.93) and HCV genotype G2 (vs G3; AOR: 5.40; 95%CI: 1.63, 17.84) were independently associated with high HCV RNA levels (>5.6 log IU/mL = 400 000 IU/mL). In conclusion, this study demonstrated that IFNL4 rs12979860 CC genotype, male sex, HIV co‐infection and HCV genotype G2 are associated with high HCV RNA levels in early chronic infection. These factors exert their role as early as one year following infection.